2010
DOI: 10.1103/physreve.81.060901
|View full text |Cite
|
Sign up to set email alerts
|

Coexistence in a one-dimensional cyclic dominance process

Abstract: Cyclic ͑rock-paper-scissors-type͒ population models serve to mimic complex species interactions. Focusing on a paradigmatic three-species model with mutations in one dimension, we observe an interplay between equilibrium and nonequilibrium processes in the stationary state. We exploit these insights to obtain asymptotically exact descriptions of the emerging reactive steady state in the regimes of high and low mutation rates. The results are compared to stochastic lattice simulations. Our methods and findings … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
21
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…For a one-dimensional version of the the rock-paper-scissors game Frachebourg and collaborators [134,135] have found that starting from some random distribution, the species organize into domains that undergo (power law) coarsening until finally one species takes over the whole lattice. Including mutation the coarsening process is counteracted and by an interesting interplay between equilibrium and non-equilibrium processes a reactive stationary state emerges [136]. The list of interesting examples, of course, continues and one may hope that in the future there will be an even more fruitful interaction between biologically relevant processes and basic research in non-equilibrium dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…For a one-dimensional version of the the rock-paper-scissors game Frachebourg and collaborators [134,135] have found that starting from some random distribution, the species organize into domains that undergo (power law) coarsening until finally one species takes over the whole lattice. Including mutation the coarsening process is counteracted and by an interesting interplay between equilibrium and non-equilibrium processes a reactive stationary state emerges [136]. The list of interesting examples, of course, continues and one may hope that in the future there will be an even more fruitful interaction between biologically relevant processes and basic research in non-equilibrium dynamics.…”
Section: Discussionmentioning
confidence: 99%
“…The simplest few species models, like the three-species rock-paper-scissors model or its four species variant, have been the subject of a range of in-depth studies that have unveiled many generic properties of systems with cyclic competition [6,7,9,8,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39,40,41,42,43,44,45,46,47,48,49,50,51,52,53,54,55,…”
Section: Introductionmentioning
confidence: 99%
“…Recent years saw a flurry of studies of systems composed of multiple species that interact in a cyclic way. Most of these studies focused on the case of three species [8,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35,36,37,38,39], a special situation where every species interact with every other species. Only rather few papers, however, dealt with more realistic cases where a given species interacts with only a subgroup of all species living in the same ecological environment [6,8,9,29,40,41,42,43,44,45,46,47,48,50,51,…”
Section: Introductionmentioning
confidence: 99%